Duplex Stainless Steel Pipes and Welded Fittings

By controlling the chemical composition and surface roughness of the two-phase stainless steel, the problems of instability and toughness of the inner scum during welding are solved, and the formation of the inner scum and the toughness of the welding heat-affected zone are achieved.

JP7623601B2Active Publication Date: 2025-01-29NIPPON STEEL CORPORATION
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022533917
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-06-23
Publication Date
2025-01-29
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

When welding two-phase stainless steel, the height of the inner scum is too high, causing corrosive fluid to stay, causing damage, and incomplete melting of the scum during welding may lead to welding defects. At the same time, the two-phase stainless steel loses the balance between austenite and ferrite after welding, affecting toughness.

Method used

By controlling chemical composition and surface roughness, we ensure the stable formation of inner scum, and adopt two-phase stainless steel pipes with specific element ratios and ranges, combined with appropriate welding processes, to form stable inner scum and maintain the toughness of the welding heat-affected zone.

Benefits of technology

The stable formation and good toughness of scum inside the welding heat-affected zone are achieved, corrosion and welding defects are avoided, and the performance of the welding part is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623601000009
    Figure 0007623601000009
  • Figure 0007623601000010
    Figure 0007623601000010
  • Figure 0007623601000001
    Figure 0007623601000001
Patent Text Reader

Abstract

This two-phase stainless steel pipe has a chemical composition of: 0.008-0.030 mass% of C; 0.10-0.70 mass% of Si; 0.80-2.60 mass% of Mn; 0.030 mass% or less of P; 0.0001-0.0050 mass% of S; 0.0004-0.0150 mass% O; 0.0001-0.0100 (exclusive of 0.0100) mass% of Sn; 0.10-2.50 mass% of Cu; 2.50-5.50 (exclusive of 2.50) mass% of Ni; 21.5-25.5 mass% of Cr; 0.10-0.50 mass% of Mo; 0.050-0.200 mass% of N; and 0.200 mass% or less of Al, with optional elements, and the balance being Fe and impurities, wherein 4S+8O+Sn is 0.0040-0.0900, and 4S+Sn is 0.0180 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to duplex stainless steel pipe and welded joints. [Background technology]

[0002] Duplex stainless steel, which is made up of ferrite and austenite phases, has high strength and good corrosion resistance in environments containing corrosive substances such as chlorides. Taking advantage of this advantage, duplex stainless steel is used as a material for pipes that transport fluids, specifically, for heat exchanger pipes in petrochemical plants and seawater treatment plants, fuel injection pipes installed in automobiles, and pipes in food plants. In recent years, duplex stainless steels that use less alloy and have further improved strength and corrosion resistance have been proposed, for example, as described in Patent Documents 1 and 2. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-168838 A [Patent Document 2] International Publication No. 2017 / 141907 Summary of the Invention [Problem to be solved by the invention]

[0004] When duplex stainless steel is used as a pipe in structures such as the above-mentioned heat exchanger and fuel injector, it may be assembled by welding. In that case, if the bead on the inner side sags and becomes excessively high, corrosive fluid may accumulate at the bead toe, which may cause the corrosive substance to thicken and cause damage. To prevent this, it is common to reduce the heat input during welding.

[0005] However, during welding, the butt surfaces may not completely melt, resulting in welding defects. In addition, in duplex stainless steel, the balance between the ferrite phase and the austenite phase in the weld heat affected zone may be lost, resulting in a loss of toughness, and this has not always been an effective measure. Therefore, in steel pipes using duplex stainless steel, it is difficult to simultaneously form an inner bead having stable and good usability performance of the weld and ensure the toughness of the weld heat affected zone.

[0006] The present invention aims to solve the above problems and provide a duplex stainless steel pipe and welded joint that stably forms an inner bead with good usability at the weld and has good toughness in the weld heat-affected zone. [Means for solving the problem]

[0007] The present invention has been made to solve the above-mentioned problems, and the gist of the present invention is the following duplex stainless steel pipe and welded joint.

[0008] (1) Chemical composition, in mass%, C: 0.008-0.030%, Si: 0.10 to 0.70%, Mn: 0.80-2.60%, P:0.030% or less, S: 0.0001~0.0050%, O: 0.0004 to 0.0150%, Sn: 0.0001% or more and less than 0.0100% Cu: 0.10-2.50%, Ni: more than 2.50% and less than 5.50%, Cr: 21.5-25.5%, Mo: 0.10-0.50%, N: 0.050~0.200%, Al: 0.200% or less, Ca: 0 to 0.0100%, Co: 0-0.80%, W: 0~0.80%, Ti: 0-0.40%, V: 0~0.40%, Nb: 0-0.40%, Ta: 0 to 0.40%, Mg: 0 to 0.0100%, B: 0~0.0100%, REM: 0~0.0800%, The balance is Fe and impurities. Fn1 represented by the following formula (i) is 0.0040 to 0.0900, A duplex stainless steel pipe, in which Fn2, represented by the following formula (ii), is 0.0180 or less. Fn1 = 4S + 8O + Sn (i) Fn2 = 4S + Sn (ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero.

[0009] (2) The chemical composition is, in mass%, C: 0.012~0.020%, Si: 0.20 to 0.60%, Mn: 1.70-2.30%, P: 0.028% or less, S: 0.0001 to 0.0015%, Cu: 0.25-2.00%, Ni: 3.50-4.50%, Cr: 22.5-24.5%, Mo: 0.20-0.40%, N: 0.100~0.180%, Contains Al: 0.020% or less, The Fn1 is 0.0050 to 0.0800, The duplex stainless steel pipe according to (1) above, wherein Fn2 is 0.0140 or less.

[0010] (3) The chemical composition is, in mass%, Ca: 0.0005 to 0.0100% The duplex stainless steel pipe according to the above (1) or (2), wherein the ratio of the Ca content to the S content, Ca / S, is 1.0 to 40.0.

[0011] (4) The chemical composition is, in mass%, Co: 0.01 to 0.80%, W: 0.01 to 0.80%, Ti: 0.01 to 0.40%, V: 0.01 to 0.40%, Nb: 0.01 to 0.40%, Ta: 0.01 to 0.40%, Mg: 0.0005~0.0100%, B: 0.0002 to 0.0100%, and REM: 0.0005~0.0800%, The duplex stainless steel pipe according to any one of (1) to (3) above, which contains one or more selected from the following:

[0012] (5) A duplex stainless steel pipe according to any one of (1) to (4) above, wherein the arithmetic mean roughness Ra on the inner surface side of the duplex stainless steel pipe in the longitudinal direction of the pipe is 9.0 μm or less.

[0013] (6) A welded joint using the duplex stainless steel pipe according to any one of (1) to (5) above. Effect of the Invention

[0014] According to the present invention, it is possible to obtain a duplex stainless steel pipe and a welded joint which can stably form an inner bead having good usability at the weld and have good toughness in the weld heat affected zone. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a diagram showing a groove shape in the embodiment. [Diagram 2] FIG. 2 is a diagram showing a groove shape during butt welding in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present inventors conducted a detailed study on butt welding of duplex stainless steel, specifically, duplex stainless steel pipes having a Cr content of 21.5 to 25.5%, a Ni content of 2.50 to 5.50%, and a Sn content of 0.0001 to 0.0100%, and obtained the following findings (a) to (e).

[0017] (a) The shape of the inner bead formed during butt welding is strongly affected by the amount of S, Sn, and O (oxygen) contained in the steel pipe. The inventors have found that if the content of these elements is low, the inner bead is not stably formed and some unmelted butt surfaces remain. On the other hand, if the content of these elements is excessive, the inner bead is stably formed, but the bead has a convex shape and the weld height is excessively high.

[0018] (b) The following are thought to be factors that affect the formation of the inner bead by these elements. S and O are surface active elements and have the effect of lowering the surface tension of the molten metal. This strengthens the inward convection in the molten pool during welding. As a result, the welding heat from the arc is easily transferred in the depth direction, allowing the inner bead to be formed stably. In addition, Sn evaporates from the molten pool surface during welding, forms a current path for the arc, and increases the current density of the arc, similarly contributing effectively to the formation of the inner bead. Therefore, the inclusion of these elements is effective in stably forming the inner bead.

[0019] On the other hand, if these elements are contained in excess, melting in the width direction becomes difficult, and the surface tension of the molten metal becomes smaller, so that even if the amount of molten metal is the same, it becomes easier to sag. As a result, the bead on the inner side becomes convex, and the bead is not formed stably. In addition, the shape of the bead on the inner side is affected by the surface roughness in the longitudinal direction of the inner surface of the pipe. And when the surface roughness is large, the bead is more likely to become convex. In particular, when the surface roughness in the longitudinal direction of the inner surface is large, the molten metal becomes less likely to spread in the width direction, and the bead on the inner side is more likely to become convex.

[0020] (c) The toughness of the weld heat-affected zone decreased with increasing S and Sn content. The following is thought to be the cause of this. As the S and Sn content increases, the ferrite phase becomes embrittled. In particular, in the weld heat-affected zone of duplex stainless steel, the proportion of ferrite phase increases compared to the base material depending on the welding thermal cycle, so the decrease in toughness is significant.

[0021] (d) Therefore, in order to stably obtain an inner bead with a good shape and to obtain good toughness of the weld heat affected zone, it is effective to contain S, Sn, and O in a range that satisfies a predetermined relationship. It is also effective to appropriately control the upper limits of the S and Sn contents.

[0022] (e) Furthermore, in order to stably obtain these performance properties, it is desirable to contain Ca within a prescribed range and to control the ratio of the Ca and S contents, i.e., Ca / S, within an appropriate range. Also, in order to obtain an inner bead with a better shape, it is desirable to control the surface roughness in the longitudinal direction of the inner surface of the pipe within a prescribed range.

[0023] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.

[0024] 1.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0025] C: 0.008 to 0.030% C has the effect of stabilizing the austenite phase, and contributes to maintaining the balance between the ferrite phase and the austenite phase in an appropriate range. In order to obtain this effect within the range of the contents of other elements, the C content is set to 0.008% or more. The C content is preferably set to 0.010% or more, more preferably set to 0.012% or more, and even more preferably set to 0.014% or more. However, if C is excessively contained, it will combine with Cr due to the welding heat cycle and form carbides at the grain boundaries in the weld heat affected zone. Then, a Cr-deficient layer will be generated near the grain boundaries, and the corrosion resistance will decrease. For this reason, the C content needs to be set to 0.030% or less. The C content is preferably set to 0.025% or less, and more preferably set to 0.020% or less.

[0026] Silicon: 0.10 to 0.70% Si is used as a deoxidizer during manufacturing. It also has the effect of stabilizing the ferrite phase and contributes to maintaining the phase balance in an appropriate range. In order to obtain this effect within the range of the contents of other elements, the Si content is set to 0.10% or more. The Si content is preferably set to 0.15% or more, more preferably set to 0.20% or more, and even more preferably set to 0.30% or more. However, if Si is contained in excess, the susceptibility to weld cracking increases. In addition, it may become difficult to stably form an inner bead. For this reason, the Si content is set to 0.70% or less. The Si content is preferably set to 0.65% or less, more preferably set to 0.60% or less, and even more preferably set to 0.50% or less.

[0027] Mn: 0.80-2.60% Mn, like Si, is contained as a deoxidizer during manufacturing. It also has the effect of stabilizing the austenite phase and is effective in maintaining the phase balance within an appropriate range. Mn also contributes to the stable formation of the inner bead. In order to obtain this effect within the range of the contents of other elements, the Mn content is set to 0.80% or more. The Mn content is preferably set to 1.00% or more, more preferably set to 1.50% or more, and even more preferably set to 1.70% or more. However, if Mn is contained excessively, the hot workability and corrosion resistance are reduced. For this reason, the Mn content is set to 2.60% or less. The Mn content is preferably set to 2.40% or less, more preferably set to 2.30% or less, and even more preferably set to 2.20% or less.

[0028] P:0.030% or less P is contained in steel as an impurity and significantly increases weld crack susceptibility. For this reason, the P content is set to 0.030% or less. The P content is preferably set to 0.028% or less, and more preferably set to 0.025% or less. It is preferable to reduce the P content as much as possible, that is, the content may be 0%, but an extreme reduction increases manufacturing costs. For this reason, the P content is preferably set to 0.001% or more, and more preferably set to 0.002% or more.

[0029] S: 0.0001~0.0050% Although S is generally contained in steel as an impurity, in the steel pipe according to the present invention, together with Sn and O, it contributes to improving the ability to form an inner bead during welding. For this reason, the S content is set to 0.0001% or more. The S content is preferably set to 0.0002% or more, and more preferably set to 0.0003% or more. However, if S is contained in excess, the inner bead becomes convex and the weld cracking sensitivity increases. Furthermore, the toughness of the weld heat affected zone decreases. For this reason, the S content is set to 0.0050% or less. The S content is preferably set to 0.0030% or less, and more preferably set to 0.0015% or less. In addition, S needs to be contained so as to satisfy the ranges of Fn1 and Fn2 represented by formulas (i) and (ii) as described later. Furthermore, it is desirable for S to satisfy the relationship with Ca as described later.

[0030] O: 0.0004 to 0.0150% O is generally contained as an impurity in steel, but in the steel pipe according to the present invention, together with S and Sn, it contributes to improving the formability of the inner bead during welding. For this reason, the O content is set to 0.0004% or more. The O content is preferably set to 0.0006% or more, and more preferably set to 0.0008% or more. However, if O is excessively contained, the inner bead becomes convex and the hot workability is reduced. For this reason, the O content is set to 0.0150% or less. The O content is preferably set to 0.0120% or less, and more preferably set to 0.0100% or less. In addition, O needs to be contained so as to satisfy the range of Fn1 represented by formula (i), as described later.

[0031] Sn: 0.0001% or more and less than 0.0100% Sn has the effect of increasing corrosion resistance, increasing penetration depth, and increasing the ability to form an inner bead. For this reason, the Sn content is set to 0.0001% or more, and Sn is intentionally included. The Sn content is preferably set to 0.0010% or more, and more preferably set to 0.0020% or more. However, if Sn is excessively included, the toughness of the weld heat affected zone decreases and the weld crack susceptibility increases. For this reason, the Sn content is set to less than 0.0100%. The Sn content is preferably set to 0.0095% or less, and more preferably set to 0.0090% or less. In addition, Sn needs to be included so as to satisfy the ranges of Fn1 and Fn2 represented by formulas (i) and (ii), as described below.

[0032] Here, Fn1 represented by the following formula (i) is set to 0.0040 to 0.0900. Fn1 = 4S + 8O + Sn (i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero.

[0033] As mentioned above, S and O act as surface active elements and strengthen the inward convection in the molten pool during welding. They then transfer the heat from the arc in the depth direction. In addition, Sn evaporates from the molten pool surface during welding, forming a current path for the arc and increasing the current density of the arc. As a result, it contributes to the stable formation of the bead on the inner side.

[0034] If Fn1 is less than 0.0040, the inner bead will not be stably formed. Therefore, Fn1 is set to 0.0040 or more. Fn1 is preferably set to 0.0045 or more, and more preferably set to 0.0050 or more.

[0035] On the other hand, if Fn1 exceeds 0.0900, the metal is difficult to melt in the width direction of the pipe, and the surface tension of the molten metal is reduced. As a result, the molten metal sags, and the bead on the inner surface becomes convex. For this reason, Fn1 is set to 0.0900 or less. Fn1 is preferably set to 0.0850 or less, more preferably set to 0.0800 or less, and even more preferably set to 0.070 or less.

[0036] Similarly, Fn2 represented by the following formula (ii) is 0.0180 or less. Fn2 = 4S + Sn (ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero.

[0037] As described above, S and Sn contribute to the formation of a stable inner bead, but excessive content of these elements embrittles the ferrite phase. In particular, in the weld heat affected zone, the ratio of the ferrite phase becomes higher than that of the base material depending on the welding heat cycle, and the decrease in toughness becomes significant. Therefore, in order to ensure the toughness of the weld heat affected zone, Fn2 is set to 0.0180 or less. Fn2 is preferably set to 0.0160 or less, more preferably set to 0.0140 or less, and even more preferably set to 0.0120 or less.

[0038] Cu: 0.10-2.50% Cu has an effect of stabilizing the austenite phase, and contributes to maintaining the phase balance between the ferrite phase and the austenite phase in an appropriate range. It is also effective in improving corrosion resistance, particularly corrosion resistance in a chloride environment. In order to obtain this effect within the range of the contents of other elements, the Cu content is set to 0.10% or more. The Cu content is more preferably set to 0.18% or more, and more preferably set to 0.25% or more. However, if Cu is contained excessively, the hot workability decreases. For this reason, the Cu content is set to 2.50% or less. The Cu content is preferably set to 2.30% or less, more preferably set to 2.00% or less, and even more preferably set to 1.70% or less.

[0039] Ni: more than 2.50% and less than 5.50% Ni has the effect of stabilizing the austenite phase, and contributes to maintaining the phase balance between the ferrite phase and the austenite phase in an appropriate range. It is also effective in improving stress corrosion cracking resistance in a chloride environment. In order to obtain this effect in the range of the contents of other elements, the Ni content is made to exceed 2.50%. The Ni content is preferably 3.00% or more, and more preferably 3.50% or more. However, since Ni is an expensive element, excessive inclusion of Ni increases the manufacturing cost. It also reduces the phase balance of the steel, and various performances are reduced. For this reason, the Ni content is made to be 5.50% or less. The Ni content is preferably 5.00% or less, and more preferably 4.50% or less.

[0040] Cr: 21.5~25.5% Cr has the effect of stabilizing the ferrite phase and contributes to maintaining the phase balance between the ferrite phase and the austenite phase in an appropriate range. It also has the effect of ensuring corrosion resistance by forming a passivation film. In order to obtain this effect within the range of the contents of other elements, the Cr content is set to 21.5% or more. The Cr content is preferably set to 22.0% or more, and more preferably set to 22.5% or more. However, excessive Cr content deteriorates the phase balance and various performances are reduced. For this reason, the Cr content is set to 25.5% or less. The Cr content is preferably set to 25.0% or less, and more preferably set to 24.5% or less.

[0041] Mo: 0.10-0.50% Mo has an effect of stabilizing the ferrite phase, and contributes to maintaining the phase balance between the ferrite phase and the austenite phase in an appropriate range. It is also effective in improving corrosion resistance, and increases strength by solid solution strengthening. In order to obtain this effect in the range of the contents of other elements, the Mo content is set to 0.10% or more. The Mo content is preferably set to 0.15% or more, and more preferably set to 0.20% or more. However, since Mo is an expensive element, if Mo is contained in excess, the manufacturing cost increases. Furthermore, a brittle phase is generated by the welding heat cycle, and the toughness of the weld heat affected zone decreases. For this reason, the Mo content is set to 0.50% or less. The Mo content is preferably set to 0.45% or less, more preferably set to 0.40% or less, and even more preferably set to 0.35% or less.

[0042] N: 0.050~0.200% N has the effect of stabilizing the austenite phase and contributes to maintaining the phase balance between the ferrite phase and the austenite phase in an appropriate range. It is also effective in improving pitting corrosion resistance and increases strength through the solid solution strengthening effect. In order to obtain this effect within the range of the content of other elements, the N content is set to 0.050% or more. The N content is preferably set to 0.080% or more, more preferably set to 0.100% or more, and even more preferably set to 0.120% or more. However, if N is contained excessively, nitrides will precipitate and ductility will decrease. For this reason, the N content is set to 0.200% or less. The N content is preferably set to 0.180% or less, and more preferably set to 0.150% or less.

[0043] Al: 0.200% or less Al is used as a deoxidizing agent during manufacturing, but if it is contained in excess, it will combine with oxygen, lowering cleanliness and impairing hot workability. In addition, it may become difficult to stably form beads on the inner side. For this reason, the Al content is set to 0.200% or less. The Al content is preferably set to 0.020% or less, more preferably set to 0.018% or less, and even more preferably set to 0.015% or less. There is no particular lower limit for the Al content, but if it is desired to obtain a sufficient deoxidizing effect, the Al content is preferably set to 0.001% or more, and more preferably set to 0.002% or more.

[0044] In addition to the above elements, Ca may be further contained within the range shown below.

[0045] Ca: 0 to 0.0100% Ca has the effect of improving hot workability by combining with S, suppresses the occurrence of defects on the inner surface of the steel pipe during manufacturing, and is effective in stably obtaining the surface roughness of the inner surface of the steel pipe described below. Furthermore, it also improves the toughness of the welded heat affected zone. For this reason, it may be contained as necessary. However, if Ca is contained in excess, it combines with oxygen, significantly lowers the cleanliness, and instead lowers the hot workability, worsens the surface roughness of the inner surface of the steel pipe, and also lowers the toughness of the welded heat affected zone. For this reason, the Ca content is 0.0100% or less. The Ca content is preferably 0.0080% or less, and more preferably 0.0060% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably 0.0005% or more. The Ca content is preferably 0.0008% or more, and more preferably 0.0010% or more. In addition, Ca needs to satisfy the relationship with S described below.

[0046] Ca / S: 1.0 to 40.0 As described above, Ca combines with S to eliminate its adverse effects and improve the hot workability and the toughness of the welded heat affected zone. In order to stably obtain this effect, it is preferable that Ca / S, which is the ratio of the Ca content to the S content, is 1.0 or more. It is more preferable that Ca / S is 1.5 or more, even more preferable that it is 1.8 or more, and most preferable that it is 2.0 or more. However, when Ca / S exceeds 40.0, Ca combines with oxygen to generate oxides, which results in a decrease in the hot workability and the toughness of the welded heat affected zone. For this reason, it is preferable that Ca / S is 40.0 or less. It is more preferable that Ca / S is 35.0 or less, even more preferable that it is 30.0 or less, and most preferable that it is 25.0 or less.

[0047] In addition to the above elements, one or more elements selected from Co, W, Ti, V, Nb, Ta, Mg, B and REM may be contained within the ranges shown below. The reasons for limiting the amount of each element will be explained.

[0048] Cobalt: 0 to 0.80% Co has the effect of stabilizing the austenite phase. Therefore, it may be contained as necessary. However, since Co is a very expensive element, if Co is contained in excess, the manufacturing cost increases significantly. Therefore, the Co content is set to 0.80% or less. The Co content is preferably set to 0.75% or less, and more preferably set to 0.70% or less. On the other hand, in order to obtain the above effect, the Co content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.

[0049] W: 0~0.80% W has the effect of stabilizing the ferrite phase. It also has the effect of improving corrosion resistance and increasing strength by solid solution strengthening. For this reason, it may be contained as necessary. However, since W is an expensive element, excessive inclusion of W increases the manufacturing cost. Therefore, the W content is set to 0.80% or less. The W content is preferably set to 0.75% or less, and more preferably set to 0.70% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.

[0050] Ti: 0 to 0.40% Ti has the effect of suppressing the generation of Cr carbides by combining with carbon to form carbides, and reducing the deterioration of corrosion resistance at grain boundaries. Therefore, it may be contained as necessary. However, if Ti is contained in excess, a large amount of Ti precipitates as carbides and carbonitrides, and ductility decreases. Therefore, the Ti content is set to 0.40% or less. The Ti content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.

[0051] V: 0~0.40% Like Ti, V combines with carbon to form carbides, suppressing the generation of Cr carbides and reducing the deterioration of corrosion resistance at grain boundaries. Therefore, V may be included as necessary. However, if V is included in excess, a large amount of V precipitates as carbides and carbonitrides, and ductility decreases. Therefore, the V content is set to 0.40% or less. The V content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.

[0052] Nb: 0 to 0.40% Like Ti and V, Nb also combines with carbon to form carbides, suppressing the generation of Cr carbides and reducing the deterioration of corrosion resistance at grain boundaries. Therefore, Nb may be included as necessary. However, if Nb is included in excess, a large amount of Nb precipitates as carbides and carbonitrides, reducing ductility. Furthermore, it also increases weld crack susceptibility. Therefore, the Nb content is set to 0.40% or less. The Nb content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.

[0053] Ta: 0 to 0.40% Ta has the effect of promoting the formation of a passive film of Cr and improving corrosion resistance. Therefore, it may be contained as necessary. However, if Ta is contained in excess, a large amount of Ta precipitates as carbides, and ductility decreases. Therefore, the Ta content is set to 0.40% or less. The Ta content is preferably set to 0.35% or less, and more preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably set to 0.01% or more, and more preferably set to 0.02% or more.

[0054] Magnesium: 0 to 0.0100% Like Ca, Mg has the effect of improving hot workability. Therefore, it may be contained as necessary. However, if Mg is contained in excess, it combines with oxygen, significantly reducing cleanliness and, conversely, reducing hot workability. Therefore, the Mg content is set to 0.0100% or less. The Mg content is preferably set to 0.0080% or less, and more preferably set to 0.0060% or less. On the other hand, in order to obtain the above effect, the Mg content is preferably set to 0.0005% or more, and more preferably set to 0.0010% or more.

[0055] B: 0~0.0100% B has the effect of segregating to grain boundaries at high temperatures, strengthening the grain boundaries, and improving hot workability. Therefore, it may be contained as necessary. However, if B is contained in excess, the weld crack susceptibility increases. Therefore, the B content is set to 0.0100% or less. The B content is preferably set to 0.0080% or less, and more preferably set to 0.0060% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0002% or more, and more preferably set to 0.0005% or more.

[0056] REM: 0~0.0800% Like Ca and Mg, REM has the effect of improving hot workability during manufacturing. Therefore, it may be contained as necessary. However, if REM is contained in excess, it combines with oxygen, the cleanliness is significantly reduced, and hot workability is reduced instead. Therefore, the REM content is set to 0.0800% or less. The REM content is preferably set to 0.0600% or less, and more preferably set to 0.0500% or less. On the other hand, in order to obtain the above effect, the REM content is preferably set to 0.0005% or more, and more preferably set to 0.0010% or more.

[0057] REM refers to a total of 17 elements, including Sc, Y and lanthanides, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of misch metal.

[0058] In the chemical composition of the present invention, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and in the manufacturing process during industrial production of duplex stainless steel, and are permissible within a range that does not adversely affect the present invention.

[0059] 2.Surface roughness of steel pipe The inner bead is formed when the end of the duplex stainless steel pipe is welded. In order to form a good inner bead, it is preferable to control the arithmetic mean roughness Ra in the longitudinal direction on the inner side of the steel pipe.

[0060] Here, the surface roughness of the alloy pipe refers to the surface roughness after the final process in the manufacturing process. That is, the surface roughness of the alloy pipe changes during the manufacturing process, but in order to obtain the effects of the present invention, the surface roughness in the longitudinal direction of the pipe after the final process does not matter, and it is sufficient if it satisfies the range specified by the present invention.

[0061] If the arithmetic mean roughness Ra of the inner surface of the duplex stainless steel pipe in the longitudinal direction of the pipe exceeds 9.0 μm, the weld metal is prevented from wetting on the inner surface of the pipe, and the weld metal is less likely to spread in the width direction, i.e., along the circumference of the pipe. As a result, the bead on the inner surface is likely to have a convex shape, and the weld height is likely to be large. For this reason, the arithmetic mean roughness Ra of the inner surface of the stainless steel pipe in the longitudinal direction of the pipe is preferably 9.0 μm or less. The arithmetic mean roughness Ra is preferably 7.0 μm or less, and more preferably 5.0 μm or less. The lower limit of the arithmetic mean roughness Ra is not particularly set, but when the manufacturing method described later is used, it is usually 0.1 to 1.0 μm or more.

[0062] The arithmetic mean roughness Ra is defined in JIS B 0601:2001, and can be measured using a contact type surface roughness measuring device.

[0063] 3. Welded joints A welded joint can be obtained by butt-welding the ends of the above-mentioned duplex stainless steel pipes together under specified conditions. A welded joint of a duplex stainless steel pipe has a weld metal, which is a joint formed by solidifying molten metal, and a base material. The base material includes a weld heat-affected zone that is affected by heat input due to welding. The base material excluding the weld heat-affected zone inherits the chemical composition, surface roughness, and other characteristics of the above-mentioned duplex stainless steel pipe. The weld refers to the weld metal and the weld heat-affected zone.

[0064] The bead width of the inner bead over the entire circumference of the welded joint is preferably 1.0 mm or more. The bead width is more preferably 2.0 mm or more. From the viewpoint of corrosion resistance, the height of the inner bead over the entire circumference is preferably 1.5 mm or less, more preferably 1.0 mm or less.

[0065] 4. Manufacturing method A preferred method for producing the duplex stainless steel pipe according to the present invention will now be described. The duplex stainless steel pipe according to the present invention can obtain the effects described above regardless of the production method, but can be stably produced, for example, by the following production method.

[0066] 4-1.Duplex stainless steel pipe First, an ingot of duplex stainless steel is produced as a raw material for the duplex stainless steel pipe. The ingot is preferably produced by melting an alloy having the above-mentioned chemical composition in an electric furnace or the like, removing impurities by refining, and then casting the melt. Note that instead of producing an ingot, a bloom may be produced by continuous casting.

[0067] The ingot is then preferably hot forged or hot rolled to form a billet. The billet is then preferably hot extruded and then cold rolled or cold drawn. During processing, softening heat treatment and intermediate pickling may be performed in between, as necessary. Then, the pipe is preferably subjected to solution heat treatment as a heat treatment. After the solution heat treatment, pickling or processing may be performed, as necessary.

[0068] Here, in order to make the arithmetic mean roughness Ra of the tube in the longitudinal direction 9.0 μm or less, it is preferable to carry out the following steps. Specifically, it is preferable to carry out the solution heat treatment under conditions of heating in the temperature range of 920°C to 1180°C for 1 to 15 minutes and water cooling. It is also preferable to carry out machining such as grinding and shot blasting or shot peening on the inner surface of the tube.

[0069] Although the surface roughness Ra changes during the manufacturing process, the effect of the present invention is affected only by the surface roughness in the longitudinal direction of the pipe after the final process, regardless of the surface roughness during the intermediate processes.

[0070] 4-2. Welded joints of duplex stainless steel pipes A welded joint can be obtained by welding the ends of the duplex stainless steel pipe according to the present invention. The welding method is not particularly limited, but may be, for example, arc welding. The conditions for arc welding are, for example, preferably a heat input in the range of 4 to 20 kJ / cm, and are preferably adjusted appropriately according to the chemical composition, groove shape, and the like. In addition, it is preferable to use Ar gas as a shielding gas and a back shielding gas during welding. The flow rate of the gas flowing through the welding portion is preferably adjusted appropriately.

[0071] The chemical composition of the welding material (filler metal) used is not particularly limited, but is preferably as follows: C: 0.050% or less, Si: 1.00% or less, Mn: 3.00% or less, P: 0.030% or less, Sn: 0.030% or less, S: 0.0001-0.0100%, Cu: 3.00% or less, Co: 10.0% or less, Ni: 4.0-10.0%, Cr: 20.0-29.0%, at least one of Mo and W in total 1.0-6.0%, at least one of Nb, Ta, Ti and V in total 1.00% or less, N: 0.05-0.35%, Al: 0.20% or less, O: 0.0004-0.0150%, Ca: 0.010% or less, with the balance being Fe and impurities. Moreover, the ratio of the Ca content to the S content, Ca / S, is preferably in the range of 0.3 to 30.0, and the contents of S, O and Sn preferably satisfy the following formula (a).

[0072] 0.0040≦4S+8O+Sn≦0.0900 (a) In the above formula, the element symbols represent the contents (mass%) of the respective elements contained in the welding material.

[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0074] Steel types A to M having the chemical compositions shown in Table 1 were melted and cast to produce ingots. The following process was then carried out to simulate the steel pipe manufacturing process. Specifically, the thickness was adjusted to 12 mm by hot forging and hot rolling. Then, the scale formed on the surface was removed by pickling. At this time, the arithmetic mean roughness Ra was about 15 μm for all steel types.

[0075] Next, some of the material was cold-rolled to a thickness of 3 mm, with softening heat treatment in between. The hot-rolled and cold-rolled materials were held at 1000°C for 10 minutes, then water-cooled for solution heat treatment. Plates 50 mm wide and 100 mm long were machined out of these materials to be used as test materials.

[0076] For the 3 mm thick test piece, which simulated the inner surface of a steel pipe, shot peening was performed on one side. For the test pieces that were not shot peened, one side was ground or polished 1 to 5 times using a grinding stone with a grit size of 40 or 60. The arithmetic mean roughness in the width direction of the shot peened, ground and polished plate surfaces was then measured using a contact roughness meter.

[0077] [Table 1]

[0078] [Table 2]

[0079] Two test pieces, each 3 mm thick, with grooves prepared as shown in Figure 1 on their longitudinal end faces were butted together and the first layer welded by automatic gas tungsten arc welding. For welding, a filler metal with an outer diameter of 1.0 mm and the chemical composition shown in Table 3 was used, and the first layer welding was performed to obtain a welded joint. The heat input during welding was approximately 5 kJ / cm, and Ar was used for the shielding gas and back shielding gas, with a flow rate of 10 L / min.

[0080] [Table 3]

[0081] For the welded joints obtained, those in which a bead was formed on the back side along the entire length of the weld line were deemed to have no problems with the ability to form a bead on the inner side of the steel pipe, and were rated as "passed." Among them, those in which the width of the back side bead was 2mm or more along the entire length of the weld line were rated as "excellent," and those in which a bead on the back side of 1mm or more was formed but was less than 2mm wide were rated as "fair." In addition, those that did not meet the criteria of "passed" were rated as "failed."

[0082] After that, three cross sections were taken from the welded joint, and in all cross sections, those in which the height of the back bead was 1.0 mm or less were judged to have a good shape of the inner bead of the steel pipe, and were rated as "passed." Among them, those in which the height of the back bead was 0.8 mm or less in all cross sections were rated as "excellent," and the rest were rated as "fair." In addition, those that did not meet the criteria of "passed" were rated as "failed." In this example, the back bead corresponds to the inner bead formed when welding from the outside of the alloy pipe.

[0083] A pair of 12 mm thick steel plates were prepared in the longitudinal direction with grooves as shown in Figure 2, then butted together and laminate welded into the groove by automatic gas tungsten arc welding. For welding, a filler metal with an outer diameter of 1.2 mm and the chemical composition shown in Table 4 was used, and the heat input was about 9 to 12 kJ / cm. Ar was used as the shielding gas and back shielding gas, and the flow rate was 10 L / min.

[0084] [Table 4]

[0085] From the obtained welded joint, three 2mm V-notch full-size Charpy impact test pieces were taken, with a notch machined 1mm from the fusion line on the vertical groove face, and subjected to a Charpy impact test. The Charpy impact test was performed in accordance with JIS Z2242:2005. The test was performed at -40°C, and the test pieces with an average absorbed energy of 100J or more were deemed "passed", and among them, the test pieces with all absorbed energy values ​​of 100J or more were deemed "passed / excellent", and the rest were deemed "passed / fair", while the test pieces with an average absorbed energy of less than 100J were deemed "failed".

[0086] [Table 5]

[0087] From Table 5, it can be seen that the test specimens obtained using the codes A to H that satisfy the chemical composition specified in the present invention have a sufficient bead on the back side and a good shape. Furthermore, it can be seen that the impact properties of the weld heat affected zone are also good. Moreover, from the test specimens A3 and A4, and B3 and B4, it can be seen that when the arithmetic mean roughness Ra of the back side satisfies the preferred range, the formability and shape of the back side bead are superior.

[0088] In contrast, for specimen J1 using code J, Fn1 was below the lower limit. As a result, melting in the plate thickness direction was insufficient, and the desired ability to form a bead on the back side could not be obtained. For specimen K1 using code K, Fn1 was above the upper limit. As a result, the molten metal sagged significantly, the height of the bead on the back side was high, and the desired bead shape could not be obtained.

[0089] In addition, in specimen I2 using the symbol I, Fn2 exceeded the upper limit. Therefore, embrittlement of the ferrite phase became significant in the weld heat affected zone, and the impact properties did not satisfy the target. In specimens L2 and M2 using the symbols L and M, the S and Sn contents exceeded the ranges specified in the present invention, respectively. Therefore, the impact properties of the weld heat affected zone did not satisfy the target. EXAMPLES

[0090] Ingots were produced by melting and casting the materials of steel types N to W having the chemical compositions shown in Table 6. Thereafter, similar to the above-mentioned Example 1, the following process was carried out to simulate the process of steel pipe. Specifically, the thickness was adjusted to 12 mm by hot forging and hot rolling. Then, the scale formed on the surface was removed by pickling. At this time, the arithmetic mean roughness Ra was about 15 μm for all steel types except for V and W. Note that V and W contained S and Ca in amounts excessive to the specified range, respectively, and therefore deep surface defects occurred during hot working, so the subsequent processes and tests were not carried out.

[0091] Next, some of the material was cold-rolled to a thickness of 3 mm, with softening heat treatment in between. The hot-rolled and cold-rolled materials were held at 1000°C for 10 minutes, then water-cooled for solution heat treatment. Plates 50 mm wide and 100 mm long were machined out of these materials to be used as test materials.

[0092] The 3 mm thick test piece was shot peened on one side to simulate the inner surface of a steel pipe, and the arithmetic mean roughness of the shot peened plate surface in the width direction was measured using a contact roughness meter.

[0093] [Table 6]

[0094] [Table 7]

[0095] As in Example 1, two test pieces with a thickness of 3 mm were butted together at their end faces in the longitudinal direction, and the first layer was welded by automatic gas tungsten arc welding. For welding, a filler metal with an outer diameter of 1.0 mm having the chemical composition shown in Table 3 was used, and the first layer was welded to obtain a welded joint. The heat input during welding was about 5 kJ / cm, and Ar was used as the shielding gas and back shielding gas, with a flow rate of 10 L / min. The obtained welded joint was evaluated according to the same criteria as in Example 1.

[0096] In the case of a thickness of 12 mm, similarly to Example 1, a pair of steel plates were subjected to groove processing shown in FIG. 2 in the longitudinal direction, butted together, and laminated welding was performed in the groove by automatic gas tungsten arc welding. For welding, a filler metal having an outer diameter of 1.2 mm and a chemical composition shown in Table 4 was used. The heat input was about 9 to 12 kJ / cm and about 15 to 20 kJ / cm. In addition, Ar was used as the shielding gas and back shielding gas, and the flow rate was 10 L / min. In addition, the steel plates with the symbols A and B shown in Table 1 were also used for the test with a heat input of about 15 to 20 kJ / cm. Therefore, the symbols A and B in Table 8 correspond to the symbols A and B in Table 1. Each welded joint was subjected to the evaluation described below.

[0097] A Charpy impact test was performed on the obtained welded joint under the same conditions as in Example 1. In addition, the absorbed energy was determined and evaluated in the same manner as in Example 1.

[0098] [Table 8]

[0099] From Table 8, it can be seen that since symbols A to H satisfy the chemical composition specified in the present invention, the test specimens obtained using these have sufficient bead formation on the back side and good shape. Furthermore, it can be seen that the impact properties of the welded heat affected zone are also good. It can also be seen that when the S and Ca contents satisfy the ranges of the present invention and the Ca / S ratio satisfies the specified range, good impact properties of the welded heat affected zone can be obtained over a wide range of welding conditions. [Industrial Applicability]

[0100] According to the present invention, it is possible to provide a duplex stainless steel pipe that can stably form an appropriate shaped inner bead during butt welding and can obtain good toughness in the weld heat affected zone. The duplex stainless steel pipe can be suitably used as heat exchanger piping in petrochemical plants and seawater treatment plants, and as fuel injection pipes mounted on automobiles.

Claims

1. The chemical composition, in mass%, is C: 0.008-0.030%, Si: 0.10-0.70%, Mn: 0.80-2.60%, P: 0.030% or less, S: 0.0001-0.0050%, O: 0.0004-0.0150%, Sn: 0.0001% or more and less than 0.0100%; Cu: 0.10-2.50%, Ni: more than 2.50% and less than 5.50%, Cr: 21.5-25.5%, Mo: 0.10-0.50%, N: 0.050-0.200%, Al: 0.200% or less, Ca: 0-0.0100%, Co: 0 to 0.80%, W: 0-0.80%, Ti: 0 to 0.40%, V: 0 to 0.40%, Nb: 0 to 0.40%, Ta: 0 to 0.40%, Mg: 0 to 0.0100%, B: 0 to 0.0100%, REM: 0-0.0800%, The balance is Fe and impurities. Fn1 represented by the following formula (i) is 0.0040 to 0.0900, On the inner surface side of a steel pipe where Fn2 represented by the following formula (ii) is 0.0180 or less, A duplex stainless steel pipe having an arithmetic mean roughness Ra in the longitudinal direction of the pipe of 9.0 μm or less. Fn1=4S+8O+Sn...(i) Fn2=4S+Sn...(ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when the element is not contained, it is set to zero.

2. The chemical composition, in mass%, C: 0.012-0.020%, Si: 0.20-0.60%, Mn: 1.70-2.30%, P: 0.028% or less, S: 0.0001-0.0015%, Cu: 0.25-2.00%, Ni: 3.50 to 4.50%, Cr: 22.5-24.5%, Mo: 0.20-0.40%, N: 0.100-0.180%, Al: 0.020% or less; The Fn1 is 0.0050 to 0.0800, The duplex stainless steel pipe according to claim 1, wherein Fn2 is 0.0140 or less.

3. The chemical composition, in mass%, Ca: 0.0005 to 0.0100%; 3. The duplex stainless steel pipe according to claim 1, wherein the ratio of Ca content to S content, Ca / S, is 1.0 to 40.

0.

4. The chemical composition, in mass%, Co: 0.01 to 0.80%, W: 0.01-0.80%, Ti: 0.01-0.40%, V: 0.01-0.40%, Nb: 0.01-0.40%, Ta: 0.01-0.40%, Mg: 0.0005-0.0100%, B: 0.0002 to 0.0100%, and REM: 0.0005-0.0800%, The duplex stainless steel pipe according to any one of claims 1 to 3, comprising one or more selected from the following:

5. A welded joint using the duplex stainless steel pipe according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Drain pipe

    JP2011105976A

  • Duplex stainless steel material for vacuum vessel and method for manufacturing the same

    JP2011168838A

  • Low carbon steel sheet excellent in cold moldability and toughness after heat treatment and manufacturing method therefor

    JP2016216809A

  • Duplex stainless steel material and duplex stainless steel pipe

    JP2017002352A

  • Duplex stainless steel material and duplex stainless steel tube

    JP2017095794A